Nurturing the winner & genius in your child strategies of highly effective parents - Khoo, Adam; Lee, Gary (Adam Khoo Learning Technologies Group, 2008)
Do you find it a challenge to constantly motivate your child to study? Does your well-intentioned advice fall on deaf ears? Do you find your child underperforming in school despite having the potential to do well? Imagine if you could discover the secrets of understanding and communicating effectively with your child. In this book, you will learn strategies in empowering your child to think responsibly and to build the motivation to succeed in school and in life.